Emerging pathological diagnostic strategies for solid pseudopapillary neoplasm of the pancreas: insights from omics and innovative techniques - Yuanhao Liu; Junya Peng; Yupei Zhao; Wenze Wang (The Journal of Pathology: Clinical Research)
Abstract Solid pseudopapillary neoplasm (SPN) of the pancreas is a rare, low‐grade malignant tumor, representing 0.9–2.7% of all exocrine pancreatic tumors. SPN patients generally have a favorable prognosis with a 5‐year survival rate exceeding 95% following complete surgical resection. Accurate diagnosis is crucial to avoid unnecessary treatments. Currently, SPN diagnosis relies on imaging techniques such as CT and MRI, along with immunohistochemical analysis of biopsy and resection samples. The main challenge in diagnosis is the potential inability to accurately identify recurrent or metastatic SPN, as well as ‘malignant’ SPN, due to the lack of specific biomarkers. Advances in high‐throughput omics technologies, including genomics, transcriptomics, proteomics and metabolomics, have opened new avenues for identifying novel biomarkers for SPN. Additional, liquid biopsy techniques have enabled more comprehensive analysis of biosamples such as pancreatic cyst fluid, offering promising prospects for preoperative diagnosis. This review highlights recent research on SPN diagnosis, focusing on immunohistochemical markers, tissue sampling methods and the potential of omics approaches. It also discusses the challenges and opportunities in improving diagnostic accuracy, particularly for high‐grade and metastatic SPNs.